2016
DOI: 10.1093/molbev/msw149
|View full text |Cite
|
Sign up to set email alerts
|

Life History of the Oldest Lentivirus: Characterization of ELVgv Integrations in the Dermopteran Genome

Abstract: Endogenous retroviruses are genomic elements formed by germline infiltration by originally exogenous viruses. These molecular fossils provide valuable information about the evolution of the retroviral family. Lentiviruses are an extensively studied genus of retroviruses infecting a broad range of mammals. Despite a wealth of information on their modern evolution, little is known about their origins. This is partially due to the scarcity of their endogenous forms. Recently, an endogenous lentivirus, ELVgv, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…The endogenous lentiviruses in rabbits 45 integrated over 12 million years (myr) ago on the basis of the presence of unambiguous orthologous copies of this virus in lapine species that diverged after this time 91 . Integration times calculated for endogenous lentiviruses detected in ferrets, lemurs and colugos further demonstrate the circulation of lentiviruses in the range of tens of millions of years [46][47][48] .…”
Section: Box 1 | Endogenous Viral Elementsmentioning
confidence: 82%
See 1 more Smart Citation
“…The endogenous lentiviruses in rabbits 45 integrated over 12 million years (myr) ago on the basis of the presence of unambiguous orthologous copies of this virus in lapine species that diverged after this time 91 . Integration times calculated for endogenous lentiviruses detected in ferrets, lemurs and colugos further demonstrate the circulation of lentiviruses in the range of tens of millions of years [46][47][48] .…”
Section: Box 1 | Endogenous Viral Elementsmentioning
confidence: 82%
“…For example, lentiviruses were originally considered as a recently emerged group of viruses on the basis of the very recent origins of HIV-1 itself and measured substitution rates that place the origins of lentiviruses to a few thousand years ago 21 . However, endogenous lentiviruses in rabbits 45 , ferrets, Madagascan lemurs and colugos demonstrate the circulation of lentiviruses over almost the entire time span of mammalian evolution [46][47][48] . In addition to retroviruses, other RNA and DNA viruses have also adventitiously integrated into host germ lines and created records of ancient infections.…”
Section: Findings From Endogenous Viral Elements and Paleovirologymentioning
confidence: 99%
“…This raises the possibility that Vif-like proteins encoded by ancestral retroviruses and/or ERVs may have exerted diversifying selective pressure on A3s. Indeed, remnants of vif genelike ORFs have been identified in endogenous lentiviruses (43)(44)(45). In addition, it has recently been reported that herpesviruses encode ribonucleotide reductase large subunits that degrade human A3 proteins (5,46,47) and that the A3 antagonists of Epstein-Barr virus and Kaposi's sarcoma-associated herpesvirus specifically recognize the loop 7 structure of A3B (5).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly referred to as viral "fossils," EVEs provide critical sequences for calibrating or informing viral phylogenies (Aiewsakun and Katzourakis 2015). One of the best examples is the discovery of lentiviral EVEs in various mammalian genomes, pushing back the evolutionary origins of lentiviruses at least 60 million years (Hron et al 2016).…”
Section: Evolutionary Ratesmentioning
confidence: 99%